CHARACTERISTICS AND POLITICAL CONNECTION TO LOCAL GOVERNMENT PERFORMANCE - Amyulianthy, Rafrini; Khair, Jessica; Lysandra, Shanti (Universitas Pendidikan Indonesia, 2016)
The purpose of this research is to find empirical evidence about local government’s characteristic and political connection to local government performance. Local government’s characteristic which were: local government age; local government wealth, dependence level of local government and regional expenditure. Political connection measured by longer the head of local government holds running the office. Local government performance measured by HDI (Human Development Index) score accessed from Indonesian Central Bureau of Statistics (BPS). The population from this research is the entire local government government in Indonesia on 2016. Total sample of this research is 80 municipal local government (kotamadya) using purposive sampling and using cross section regression analysis. The results of this research is shows that from characteristic, local government wealth and dependence level of local government has positive significant to local performance, while political connection also has positive significant to local performance. Meanwhile, local government age and regional expenditure has no significant effect to local government performance.